EUPHEMISM AND DYSPHEMISM IN BLACK PANTHER: A SOCIOPRAGMATIC ANALYSIS OF POWER AND IDENTITY - Santosa Santosa; Masami Permana; Radik Darmawan; Theresia Mundi Astuti; Bayu Andika Prasatyo (English Education Department at FKIP Nommensen University, 2026)
Language functions as a strategic tool for regulating social interactions and power dynamics through provocation or politeness. This study investigates the use of euphemism and dysphemism in the film Black Panther, focusing on how characters manage sociopolitical tensions. Utilizing Allan and Burridge’s (2009) framework, this qualitative research analyzed 12 linguistic items identified within the film’s screenplay. The data were categorized through a three-stage analytical procedure: classification, description-interpretation, and theoretical synthesis. The results indicate a significant dominance of euphemisms (8 items or 66%) over dysphemisms (4 items or 34%). Euphemisms primarily function as a